An extremely narrow band gap conjugated polymer for photovoltaic devices covering UV to near-infrared light. (November 2018) - Cao, Xiaodong; Tong, Junfeng; He, Zhicai; Zhang, Mingjing; Zhang, Xiaofang; Ma, Jun; Gao, Peili; Li, Jianfeng; Zhang, Peng; Wang, Chenglong; Xia, Yangjun; Wu, Hongbin
Abstract: An alternating narrow band gap conjugated polymer derived from 4, 6-bis(4-tetradecylthien-2-yl)thieno[3, 4- c ]thiadiazole and thieno[3, 2- b ]thiophene, was synthesized by Stille coupling reaction, and named as PDTTZ-TT. The resulted polymer exhibits good solution processability, and extensive light absorption ranging from 300 nm to 1260 nm with optical band gap of 0.98 eV in solid state. The highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energy level of the polymer determined by the cyclic voltammetry (CV), are about −4.96 eV and −3.98 eV, respectively. Prototype regular photovoltaic devices ( r -PDs) based on the blend films from PDTTZ-TT and [6, 6]-phenyl-C61 butyric acid methyl ester (PC61 BM) or [6, 6]-phenyl-C71 butyric acid methyl ester (PC71 BM) with the configuration as ITO/PEDOT:PSS/blend film/Ca/Al, provided power conversion efficiencies (PCEs) of 0.65% and 1.12% with light response from 300 nm to 1260 nm under AM 1.5 G with irradiation of 100 mW cm −2 . The corresponding specific detectivity of the r -PDs based on the blend films of PDTTZ-TT/PC61 BM and PDTTZ-TT/PC71 BM at 875 nm was reached to about 1.86 × 10 12 and 4.65 × 10 12 Jones under zero bias. The PCEs of the inverted photovoltaic devices ( i -PDs) with the configuration as ITO/PFN/active layers/MoO3 / Ag, in which PFN ((poly (9, 9-bis(3′-( N, N -dimethylamino)propyl)-2, 7-fluorene)- alt -2, 7-(9, 9-dioctylfluorene)) was employed as cathode modification layer, were improved to 1.45%. Meanwhile, the dark current density of the i -PDs was decreased to 3.23 × 10 −7  mA cm −2 and the specific detectivity at 870 nm was reached to 7.66 × 10 12 Jones under zero bias. As we have known, it is one of the best reported sensitivity for polymer photodetectors with light response covering UV-Vis to near-infrared light. Graphical abstract: An alternating narrow band gap conjugated polymer derived from 4, 6-bis(4-tetradecylthien-2-yl)thieno[3, 4- c ]thiadiazole and thieno[3, 2- b ]thiophene, was synthesized by Stille coupling reaction, and named as PDTTZ-TT. Photovoltaic devices from the PDTTZ-TT and fullerene derivatives exhibit light response from 300 nm to 1260 nm. The specific detectivity of the devices was reached to 1.68–7.66 × 10 12 Jones under zero bias. As we have known, it is one of the best reported sensitivity for polymer photodetectors with light response covering UV-Vis to near-infrared light. Image 1 Highlights: An extremely NBG thieno[3, 4- c ]thiadiazole-based conjugated polymer PDTTZ-TT absorbing UV-Vis to NIR is presented. A specific detectivity of 1.68–7.66 × 10 12 Jones in a broad spectral region of 300–1260 nm under zero bias was achieved. PDTTZ-TT is one of the best reported sensitivity for polymer photodetectors with light response covering UV-Vis to NIR.